Psychometric Properties Of Leiden Index Of Depression Sensitivity-Revised (LEIDS-R) In Persian Language - Ostovar, Shahla (2012)
Currently no valid or reliable self-report instrument exists in the literature for recovered depressed (RD) individuals to use in evaluating cognitive reactivity (CR). CR is the degree of change in negative thinking in response to sad mood, and it has been found to play a key causal role in depressive relapse. The present study aims to develop and validate a Persian-language version of LEIDS-R for use by psychologists’ and clinicians’ centers in Iran. LEIDS-R was translated into Persian and the content validated by experts’ judgment.